Prosedur Penanganan Reservasi Tiket Lion Air Group Di PT Bali Daksina Wisata - Kurniawati, Maria Anjelina; Anggara, I Gusti Made Dwi Candra; Kardana, I Ketut (Jurnal Daya Tarik Wisata, 2025)
PT Bali Daksina Wisata Tour and Ticketing is a travel agency that serves Lion Air Group airline ticket bookings. This research is motivated by the importance of understanding effective reservation handling procedures to maintain customer satisfaction. The purpose of this study is to determine the stages of the ticket reservation procedure, identify the obstacles faced during the reservation process, and analyse the resolution efforts made by the staff. This research uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that the reservation procedure is carried out through five stages, namely customer requests, searching schedules and prices through the Agent Portal system, collecting passenger data, payment, and ticket issuance. In practice, staff often face obstacles such as limited seats, errors in filling in passenger data, delays in replenishing system balances, and internet connection disruptions. To overcome this, staff coordinate with the finance department, remind customers of the time limit for confirmation, and use a private network during technical disruptions. The conclusion of this study shows that the effectiveness of reservation procedures is highly dependent on the accuracy of the system, communication between staff, and the speed of response to problems. This research contributes to the development of operational management of travel agencies, especially in flight ticket reservation services.